Caracterização parcial e desenvolvimento de oligonucleotídeos específicos para detecção de sequivírus infectando alface - Jadão, Adriana Salomão [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
A família Sequiviridae é constituída por dois gêneros: Waikavirus e Sequivirus. Os vírus apresentam partículas isométricas com aproximadamente 30nm de diâmetro e uma única fita de RNA sentido positivo, sendo que o genoma dos waikavírus é poliadenilado e dos sequivírus não. Dandelion yellow mosaic virus (DaYMV) foi relatado infectando alface em diferentes países da Europa e classificado no gênero Sequivirus, porém dados moleculares não estão disponíveis para este vírus. No Brasil, um vírus isométrico infectando alface foi isolado por Marinho et al., (1982) no Distrito Federal e denominado de Lettuce mottle virus (LeMoV). Um provável isolado deste vírus isométrico foi descrito mais tarde no estado de São Paulo por Stangarlin (1995), sendo encontrado frequentemente em infecções mistas com o Lettuce mosaic virus (LMV). Em ensaios de microscopia eletrônica utilizando antissoro policlonal específico para Dandelion yellow mosaic sequivirus (DaYMV) e extrato foliar de plantas infectadas pelo LeMoV, foi verificada uma reação sorológica parcial (Chaves, 1999), indicando que o LeMoV possivelmente seria um membro do gênero Sequivirus, família Sequiviridae. Um protocolo funcional de purificação tanto para o LeMoV como para o DaYMV foi desenvolvido e sequências parciais do genoma de ambos os vírus foram obtidas usando preparações virais purificadas e...

The Sequiviridae family is constituted by two genus: Waikavirus and Sequivirus. The virus have approximately 30nm of diameter and a single-stranded of positive sense RNA. The genome of waikavirus is polyadenylated and of sequivirus not. Dandelion yellow mosaic virus (DaYMV) was reported in different countries of the Europe infecting lettuce and classified in the Sequivirus genus however, molecular data are not available for this virus. In the region of Federal District, Brazilan isometric virus infecting lettuce was isolated by Marinho et. al., (1982) and called of Lettuce mottle virus (LeMoV). Probable a strain of this isometric virus was described later in the Sao Paulo state by Stangarlin (1995), frequently found in mixed infections with the Lettuce mosaic virus (LMV). Using specific polyclonal antiserum for Dandelion yellow mosaic sequivirus (DaYMV) and foliar extract of plants infected for the LeMoV, a partial serological reaction was verified for this virus (Chaves, 1999), indicating that the LeMoV could be possibly a member of Sequivirus genus, Sequiviridae family. A functional protocol of purification was developed for LeMoV and DaYMV and partial genome sequences for both virus was obtained using virus purified preparation and degenerated primers for the Sequiviridae family. Sequences of the LeMoV-AF197 and the DaYMV-DSM2 were analyzed and showed a high identity with other members of the family. Universal primers that detect both viruses and specifics primers for LeMoV and DaYMV were used in diagnosistic tests based on RT-PCR. The specific primers amplified one fragment of 300bp for the LeMoV and 331bp for the DaYMV, being highly specific for diagnosis because no antiserum with good properties are available for these viruses. Different sequivirus proceeding from Brazil (BR11), Chile (Ch36), Holland (DSM2) and France (2227) were also evaluated in this work... (Complete abstract click electronic access below)
Keywords: Alface; Alface - Vírus isométrico; Lettuce - Isometric virus